If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 15 = 10x + -35 Reorder the terms: 15 + 5x = 10x + -35 Reorder the terms: 15 + 5x = -35 + 10x Solving 15 + 5x = -35 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 15 + 5x + -10x = -35 + 10x + -10x Combine like terms: 5x + -10x = -5x 15 + -5x = -35 + 10x + -10x Combine like terms: 10x + -10x = 0 15 + -5x = -35 + 0 15 + -5x = -35 Add '-15' to each side of the equation. 15 + -15 + -5x = -35 + -15 Combine like terms: 15 + -15 = 0 0 + -5x = -35 + -15 -5x = -35 + -15 Combine like terms: -35 + -15 = -50 -5x = -50 Divide each side by '-5'. x = 10 Simplifying x = 10
| 2+x-(5+2x)-7=-2x+7 | | 56-9x=56-17x | | 3(x+3y)-4(2x-5y)= | | -16+p=28 | | (y^2)-1.5y-7=0 | | 17x-84=3x+56 | | y+4=2y | | 19x-44=8x+88 | | 56-6x=49-13x | | 16x-30=1x-15 | | 4x-33=15x+44 | | 15x+152=38-4x | | 8-9x=10-11x | | 13x+30=15-2x | | 5-(-2x-3)=4x-(3x-8) | | 18-11x=21-14x | | 18x+42=4x-28 | | 42-17x=28-3x | | 12x+56=5x-42 | | 18x-32=2x-112 | | 2(3x+4)=34-2x | | 12x-25=7x-30 | | 3x-91=16x+117 | | -71(n)=-71(n-1)4.2 | | 8x-32=16x+48 | | 10X+18=1X-63 | | F(1)=-71 | | 6X-112=20X-42 | | a^3+b(3+c)(4-c)=0 | | 7-5x=56-12x | | 17x+84=5x-84 | | a+(24395+15606+36859+12897)=178934 |